Profiting from Parity : Unlocking the Potential of Women's Business in Africa - World Bank Group (World Bank, Washington, DC, 2019)
Sub-Saharan Africa has the highest rate of entrepreneurship in the world, with approximately 42 percent of the non-agricultural labor force classified as self-employed or employers. Yet most entrepreneurs are unable to grow their businesses beyond small-scale subsistence operations, impeding their contribution to poverty reduction and shared prosperity. This is particularly so for women. This new report, “Profiting from Parity: Unlocking the Potential of Women’s Businesses in Africa”, produced by the World Bank Group’s Africa Gender Innovation Lab and the Finance, Competitiveness and Innovation Global Practice, seeks to focus attention on the challenges that Africa’s women entrepreneurs face and identify practical solutions. The report draws on new, high-quality, household and firm level data to present the clearest evidence to date about the barriers to growth and profitability faced by women entrepreneurs. It goes beyond looking at contextual, endowment and household restrictions in isolation, and, through deep-dive analysis, uncovers new evidence on how social norms, networks and household-level decision making contribute to business performance. It analyzes how they are linked to each other and to women’s strategic business decisions. The report offers policy makers evidence based guidance on designing programs to target multiple obstacles and improve the performance of women entrepreneurs.